PENERAPAN WEIGHTED K-MEANS DAN HEATMAP OVERLAY UNTUK REKOMENDASI LOKASI STRATEGIS UMKM KOPI KELILING: IMPLEMENTATION OF WEIGHTED K-MEANS AND HEATMAP OVERLAY FOR STRATEGIC LOCATION RECOMMENDATION OF MOBILE COFFEE MSMES - Ridho Alif Naufaldy; Asep Wahyudin; Herbert Siregar (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Determining the operational routes for MSME mobile coffee vendors currently relies on subjective intuition, leading to time inefficiencies and income fluctuations. This study designs a mobile-based Decision Support System (DSS) using a Prototyping approach to provide objective strategic location recommendations. The system processes 10,961 historical transactions using the Weighted K-Means algorithm. Cluster center determination is modified using the center of mass principle based on profit and sales quantity weights, then visualized through a heatmap overlay. Functional testing using the Black Box method confirmed that all application parameters are valid. Field trials empirically demonstrated the system's effectiveness through a 16.6% surge in the fleet's average daily net profit (from Rp1,654,254 to Rp1,929,709). In conclusion, this DSS has proved to be successful in transforming conventional route determination into a data-driven precision strategy to boost MSME profitability.